2018
DOI: 10.1186/s12889-018-5214-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex tourism among Chinese men who have sex with men: a cross-sectional observational study

Abstract: BackgroundSex tourism among men who have sex with men (MSM) may exacerbate transmission of HIV and other sexually transmitted infections (STIs). Sex tourism is defined as purchasing sex with gifts or money outside of one’s hometown. Our objective was to characterize the frequency, socio-demographic characteristics, and sexual risk behaviors among Chinese MSM sex tourists.MethodsAn online, cross-sectional survey for high-risk MSM throughout China was conducted in November 2015 covering sociodemographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…In China, several HIV risk behaviors were observed among MSM who practiced sex tourism. These behaviors include sexual intercourse without condoms and sex with multiple partners [ 31 ]. In addition, another previous study in China showed the municipalities with high density populations and high economic growth had higher HIV population-level diagnosis rates among MSM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, several HIV risk behaviors were observed among MSM who practiced sex tourism. These behaviors include sexual intercourse without condoms and sex with multiple partners [ 31 ]. In addition, another previous study in China showed the municipalities with high density populations and high economic growth had higher HIV population-level diagnosis rates among MSM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has become clear that sex tourism poses a substantial risk of infection. Sex tourism leads to risky sexual behaviors, such as unprotected anal intercourse, forgoing condom use, and other behaviors that increase HIV risk [50,51,52], amplifying regional HIV epidemics [53]. Considerable change in sexual behaviors has been observed through modernization in Asian cities such as Hanoi, Shanghai, and Taipei [54].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characteristics examined in this study included sociodemographic characteristics (age, education, income, student status, marital status, province of residence), sexual identity, HIV/syphilis testing history and HIV status, and sexual behavior (sex under the influence of alcohol, group sex, sex tourism, receptive anal sex with stable/casual male partners). Sex tourism was defined as having traveled outside of the city of residence to purchase sex with gifts or money [14]. Community engagement in sexual health was assessed at baseline.…”
Section: Methodsmentioning
confidence: 99%